Perilaku Pencegahan Penularan Covid-19 Pada Ibu Hamil - Sari, Lilik Nur Indah; Budiono, Irwan (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2021)
Background: Pregnant women and unborn babies represent a high-risk population during outbreaks of infectious disease such as Covid-19. In Ngargoyoso there are 14 pregnant women who have been confirmed positive Covid-19. But in reality, the Covid-19 prevention behavior is still lacking, 60% of pregnant women do not use masks when doing activities outside the home at close range, 80% do not keep their distance when in a crowd. This study aims to determine the factors associated with Covid-19 prevention behavior in pregnant women. Methods: This type of research is an observational analytic study using a cross sectional design. Simple random sampling technique and a sample of 105 respondents. The research instrument used a questionnaire and used the Chi Square test. Results: There is a relationship between level of knowledge (0.044), attitude (0.009), parity (0,027), and family support (0.000) with the behavior to prevent the transmission of COVID-19 in pregnant. There is no relationship between COVID-19 transmission prevention behavior in pregnant with health workers support (0.482), and information exposure (0.181) Conclusion: There is a significant relationship between the level of knowledge, attitudes,parity, and family support, with the behavior to prevent COVID-19 transmission in pregnant. Keywords: COVID-19, Pregnant, Preventive Behavior